THE INFLUENCE OF THE EFFECTIVENESS AND CONTRIBUTION OF LAND AND BUILDING TAXES ON THE REGIONAL INCOME OF SURABAYA: EMPIRICAL STUDY: ON THE REGIONAL REVENUE AGENCY OF THE CITY OF SURABAYA - Pitaloka, Rike Diya Ayu; Widajantie, Tituk Diah (Yayasan Education and Social Center, 2024)
This research aims to test and prove the extent to which the effectiveness of Land and Building Tax revenues affects the Regional Original Income of the City of Surabaya during the 2018-2022 period. This type of research is quantitative research. The population and sample of this research are a Report on the Realization of Regional Original Income and a Report on the Realization of Regional Taxes for the City of Surabaya from 2018 to 2022. The data analysis technique used is Statistical Package for Social Science (SPSS) software as well as hypothesis testing with the t-test, F test, and coefficient of determination. The results of this research show that the effectiveness of Land and Building Tax has an influence on the Original Regional Income of the City of Surabaya in 2018-2022, while the contribution of Land and Building Tax has no influence on the Original Regional Income of the City of Surabaya in 2018-2022